Quality of primary health care services in rural Bangladesh: patients’ perspectives - Hasan, Md. Kamrul (© 2012 Ontario International Development Agency, Canada, 2016)
This article was published in OIDA International Journal of Sustainable Development [© 2012 Ontario International Development Agency, Canada] and the definite version is available at : http://www.oidaijsd.com/Files/3-8-7.pdf The article website is at: http://www.oidaijsd.com/20140/160688/a/quality-of-primary-healthcare-services-in-rural-bangladesh-patients-perspectives